Asian affinities and disparities with modern architecture and the Philippine adaptation - Bulaong, Carmen Bettina S. (2014)
Modern formulated its Architectural idiom from a most unlikely wellspring : Southeast Asia turned out to be a source of overflowing inspiration for western art and architecture, particularly, when Japan had re-opened its doors to trading with the West in the 19th century after more than two centuries of national isolation. It is from this influx transcultural architecture gestated. This is the architecture of a turn-of-the-century European concept that stemmed from the rapid advancement in technology and the search for a new style that signified modernity, progress and power. This is the architecture that a growing middle class society would espouse.

This paper discusses how, on one hand, many scholars and architectural theorists claim that Modern Architects were inspired by the traditional Japanese and Southeast Asian Architectural language in its bid for universality. However, it is the author's observation that there is very little discussion as to how and what physical attributes of these Modern styles were actually derived from the traditional Southeast Asian architectural characteristics, forms and elements. It is therefore the author's objective to support these claims by presenting some parallelisms between the features and nuances of traditional architecture of this region and those of Modern Architecture. Such parallelisms include the Minimalist style and the concept of "Less is More," the Open Plan System, the Sliding Panel Doors and the Shoji, the Framing System and the Non-load bearing walls, the Asian structures on stilts and the Piloti, as well as the concept of the Ribbon Windows. The author's procedure of inquiry includes looking into the historicity of these concepts in the Western building tradition to be able to say whether or not these concepts were derived and adapted by Modernist architects as evident in their masterpieces in Europe, United States, Israel, Latin America, as well as Asia.

On the other hand, the author also holds that Modern Architecture presented some disparities with the Southeast Asia tradition of building because it is not the context that it was originally intended for. It is the author's methodology to analyze these incongruous features, which included the use of the flat roof and the use of modern materials such as glass and steel, in terms of how they performed in providing thermal comfort conditions in modern buildings located in a country with a tropical environment such as the Philippines. The author is of the opinion that response-to-context is one of the reasons why modernist architects found the need for further confirmation of this new style to local customary patterns in building, creating their own composite, transcultural style. Thus, as Cabalfin would put it, "... a foreign concept is made understandable to the local audience by referring to familiar local materials and ideas".